Wacana Gender dan Relasi Kuasa dalam Cerpen Kuzuha No Issei Karya Matsuda Aoko (Humanis, 2026)
This study aims to analyze the issues of gender gap in contemporary Japanese society that represented in the short story of Kuzuha no Issei, along with the things that had been became the roots of these problems. Because the issue of gender gap was influenced by social constructions and stereotypes, this study will use a general gender theory approach and associated with Michael Foucault’s power relations. The result shows there are six gender gap issues that arise in the short story of Kuzuha no Issei. That was ‘women should not stand out’, ‘women and simple jobs’, ‘someone ability was judged by gender’, ‘women as housewives’, ‘demure Japanese women’, and  ‘women and men as the victims of government discourses’. This phenomenon was influenced by the patriarchal system, IE, traditional gender stereotypes such as ryōsai kenbo and yamato nadeshiko, as well as the discourses in Japanese society which had been normalized to form doctrines and social constrctions.
Keywords: gender gap; discourse; Kuzuha no Issei; women